Tool for estimating scope of building damage based on results of geometric operations between elements in building information models - Michio Matsubayashi (Journal of Asian Architecture and Building Engineering)
As a building ages, various types of problem caused by issues such as water leakage become more likely. Building information models (BIMs) are becoming more commonly used in the design and construction phases. Effort has been expended to also make them more effective in the maintenance phase. This study develops an add-on tool for predicting the scope of water leakage using the results of geometric operations between different elements in a BIM. A case study of water leakage associated with deteriorating rooftop waterproofing is presented. The development of the tool is based on interviews and a literature survey. The process of water spreading from a starting spot is described using multiple stages. A drawing on a plan view and calculation results based on the number of elements are presented to the user. The developed add-on tool is evaluated using a case study on some rooms in a BIM. The proposed tool can represent the knowledge and experience related to facility management using BIM technology. The novelty of the proposed tool is that it focuses on the detailed geometry and exact placement of elements in a BIM used for maintenance purposes and uses these elements in edited form.